Land/ Sea Breeze Circulation Systems of Churchill, Manitoba - Holland, Susan (1989)
This research paper was submitted to the Department of Geography in fulfilment of the requirements of Geography 4C6. This research details the presence of the land/ sea breeze circulation system near Churchill, Manitoba. Data collected from June 6 to August 13, 1987 were analyzed with respect to wind direction, temperature and vapour pressure to determine the effects of the system on the climate. Results indicate that there is a seasonal progression in wind frequency from dominantly onshore (42% of the time) to dominantly mixed winds (75% of the time). The frequency of the land/ sea breeze increases across the season. Smaller wind velocities, colder temperatures and larger vapour pressures are associated with onshore winds, while offshore winds have greater velocities, higher temperatures, and smaller vapour pressures. Offshore winds are 5-7°C warmer than onshore winds. The sea breeze is larger than the land breeze by a 3:2 ratio. Thesis Bachelor of Arts (BA)